GENESIS OF SOCIOCULTURAL COMPETENCE DEVELOPMENT AS A PEDAGOGICAL ISSUE IN UKRAINE AND POLAND (Comparative Professional Pedagogy, 2023)
The article provides an analysis of Ukrainian and Polish scientific works, which highlight the formation and development of sociocultural competence as a pedagogical issue, which is a key component of the competence paradigm in Ukraine and Poland in late 20th – early 21st century. The essence of the concepts and constructs of «competent», «competence», «socio-cultural competence» is analyzed. Competence is the qualities of a person that help them to practically use acquired knowledge, abilities and skills and to apply them in specific life circumstances. In modern psychological and pedagogical literature it is implemented in the context of several scientific approaches, in particular, communicative, sociocultural, activity, contextual and informational. Initially, the notion of «sociocultural competence» was coined by J. Cummins, a Canadian scientist in the field of applied linguistics.According to modern Ukrainian and Polish researchers, sociocultural competence reveals the integrative intercultural qualities of the individual, which are acquired, assimilated and implemented by pedagogical activity in a multicultural environment. The circle of Ukrainian and Polish scientists who studied the issues of the competence paradigm is outlined. The components in the structure of sociocultural competence are singled out. The article presents periodization in the development of sociocultural competence as a pedagogical phenomenon in Poland in late 20th – early 21st century, which was elaborated by L. Smirnova, who carried out an analysis of the historical prerequisites and reforms of higher education system in Poland. In the second half of the 20th century, under the influence of social, political and cultural changes in Poland and Ukraine, a sociocultural component was considered a basis of professional education, and in early 21st century, sociocultural competence was reconsidered and became a mandatory key component of modern education. The process of forming sociocultural competence in Ukraine and Poland is analyzed.
Keywords: competent; competence; competency; sociocultural; sociocultural competence; competency paradigm; genesis